Characterising the influence of cerebellum on the neuroplastic modulation of intracortical motor circuits. - George M Opie; John G Semmler (PLoS ONE, 2020)
The cerebellum (CB) has extensive connections with both cortical and subcortical areas of the brain, and is known to strongly influence function in areas it projects to. In particular, research using non-invasive brain stimulation (NIBS) has shown that CB projections to primary motor cortex (M1) are likely important for facilitating the learning of new motor skills, and that this process may involve modulation of late indirect (I) wave inputs in M1. However, the nature of this relationship remains unclear, particularly in regards to how CB influences the contribution of the I-wave circuits to neuroplastic changes in M1. Within the proposed research, we will therefore investigate how CB effects neuroplasticity of the I-wave generating circuits. This will be achieved by downregulating CB excitability while concurrently applying a neuroplastic intervention that specifically targets the I-wave circuitry. The outcomes of this study will provide valuable neurophysiological insight into key aspects of the motor network, and may inform the development of optimized interventions for modifying motor learning in a targeted way.